The pattern of maxillo-facial fractures in Hospital Univerrsiti Sains Malaysia : a retrospective study of recent 5-years - Patowary, Md Hosain Shohid Shoraourddi (2020)
Patterns of maxillofacial fracture are found to be changing with the period of time depending upon socio-economic condition, geographical position, education and cultural status of a society. Therefore the periodic recent retrospective data analysis is important to provide the information to the involved parties for taking the necessary actions to reduce number and the fatality of maxillofacial fractures as well as confer effective and fast management. The objectives of this study were to assess the most common type of facial bone that prone to fracture, main etiological factor, correlations between the fractured facial bones, association of age and gender with the types of facial bone fractured and the treatment modalities provided by the OMFS unit, hospital USM, Kelantan, Malaysia. This was a retrospective crosssectional, descriptive analysis based on the medical records of the maxillo-facial fracture patients that was treated in the OMFS unit, Hospital USM, Kelantan, Malaysia, over a period of five years from 2012 to 2016. A pre-designed data collection chart was used to collect data from patients’ medical record. The collected data was analyzed by descriptive statistics and the Chi-square Test in SPSS 23.0 software. Total 209 cases of maxillo-facial fractures were included, out of those 167 males and 42 females; age range was 0-70 years and above. The most responsible etiological factor for maxillofacial fracture was road traffic accident, 90.4% and males of 21-above years age group were predominantly affected. The concomitant zygomatic complex fracture was mainly affected site (86.1%) followed by fracture in the orbital area (69.9%). There was a strong significant correlation in case of zygoma with orbital fracture and maxilla with Le fort I and le fort II fracture in midface whereas in lower face mandibular symphysis fracture had a significant moderate correlation with condylar fracture. In general, there was no significant association of maxillofacial fracture with the age and sex. 45.5% cases were treated surgically and 39.2% cases by conservative technique.